Value chain of the data-poor Chinese bay scallop aquaculture. (April 2023) - Yu, Lance; Tan, Xiaolan; Guan, Xiaomu; Mu, Yongtong; Lam, Vicky; Sumaila, Rashid
Abstract: Despite a tremendous growth and the huge commercial size at present, the Chinese bay scallop aquaculture is quite data-poor, which induces a series of vacuum, inefficiency, and mismatch in management and heavily impedes its transformation and upgrading. Here, we conduct the value chain analysis on it using an innovative approach that performs quantitative evaluations from micro-perspective to present the more detailed picture without relying on official statistics. We find that one parent scallop costs 0.14 USD and is given a value increase of 84.94 USD, equivalent to over 600 times higher than its initial value, by four production nodes of the value chain. There is no obvious regularity reflected in value increase among nodes due to the complexity conspired by variable increment rates and growing cardinal numbers, but a downward trend of profitability along the value chain looms. We recognize that it is not an individual case and closely related to high transaction costs, suggesting that, enhancing the horizontal integration of businesses in a certain node can not make the aquaculture production more efficient, while there remains a need for the vertical integration of different nodes to improve management effectiveness.